FRITZ ZWICKI'S MORPHOLOGICAL APPROACH TO THE DESIGN OF INTEGRATED PROTECTION SYSTEMS FOR INFORMATION AND COMMUNICATION FACILITIES - I. S. Klimenko (Современная наука и инновации)
The methods of describing complex systems, which is certainly the complex protection of infocommunication objects, are divided into quantitative and qualitative. The fundamental difference lies in the approaches to the formulation of the problem, to finding possible solutions and their evaluation.